University students' transformation of meanings within an ESP digital context - Christoforou, Maria (My University, 2022)
Visual manifestations of meanings can provide an important means of creativity in educational contexts. In fact, the unprecedented technological advancements and their multimodal affordances have enriched the visual communicational landscape, initiating more interactive literacy practices for students to enter a transformative process of meaning-making, design multimodal texts and remake new representations of the world. This qualitative study explores the concepts of “transmediation”, “transformation”, and “design” as seen in university students’ meaning-making and representation of course content projected through digital semiotics in a technology-enhanced, language course. Specifically, it interprets the semiotic modes from the students’ visual/multimodal designed texts and analyses transmediation from visual to verbal modes to see the multiplication of meaning in the move across sign. Data were collected through multimodal analysis and semi-structured interviewing with six Fine Arts students in an English-for-Specific-Purposes (ESP) course, conducted exclusively online due to the pandemic. Thematic analysis pertains to the interview as an ongoing, dynamic performance of the sign-makers’ strong sense of subjectivity and world representation. An important revelation is the prevalence of the written mode in the digital context, which points to the discourses that permeate digital production within academic contexts and which are part of the available designs that speak of established social rationalities and familiar representations.
Keywords: ESP; Transmediation; Design; Transformation; Multimodality